1996
DOI: 10.1016/0042-6989(95)00259-6
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficiency for the Detection of Apparent Motion **We are indebted to an anonymous referee for suggesting this possibility and the test to exclude it.

Abstract: We measured the relative efficiency for motion and position discriminations of brief, localized spot stimuli with a technique that makes no assumptions about sites of noise or information loss in the visual system. In one task, the observer had to discriminate whether an increment was located at one (left) or another (right) closely spaced spots. In the other task, the observer had to discriminate two successive brief increments of the left spot from a left spot increment followed by a right spot increment. Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Moving objects resulted in longer detection distances compared to static objects which is in agreement with current literature (Abrams & Christ, 2003;Bhagavathula, et al, 2012;S. Franconeri & Simons, 2003;Gros, et al, 1996). From the results of this study motion seems to draw more attention than expectancy when it comes to detecting new objects at nighttime on roadways.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moving objects resulted in longer detection distances compared to static objects which is in agreement with current literature (Abrams & Christ, 2003;Bhagavathula, et al, 2012;S. Franconeri & Simons, 2003;Gros, et al, 1996). From the results of this study motion seems to draw more attention than expectancy when it comes to detecting new objects at nighttime on roadways.…”
Section: Discussionsupporting
confidence: 94%
“…Research has shown that motion is a predictor in detecting new objects, irrespective of their luminance. Moving objects were said to be detected more efficiently than static objects (Gros, Pope, & Cohn, 1996). Studies have also indicated that only objects that create some sort of motion or luminance based transient effect can be detected by observers easily (Abrams & Christ, 2003;Enns, Austen, Di Lollo, Rauschenberger, & Yantis, 2001;S.…”
Section: Introductionmentioning
confidence: 99%
“…We have directed our attention at a class of visual stimuli that others have found the eye to be most sensitive to. Previous research has demonstrated that stimuli that move or that appear to move have lower detection thresholds, and thus are seen more easily (Gros et al 1996;Watson et al 1983). Our present experiments demonstrate that moving stimuli also produce faster reaction times than stationary targets.…”
Section: Introductionsupporting
confidence: 66%